The Effect Of Organizational Transformation And Leadership On Employee Performance Mediated By Organizational Behavior At PT Angkasa Pura Aviasi Kualanamu Airport - Noval Charunia; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study aims to examine the influence of organizational transformation and leadership on employee performance with organizational behavior as an intervening variable. The number of respondents involved in this study was 42 respondents, all of whom were employees of PT. Angkasa Pura Aviation Kualanamu International Airport. This study uses a quantitative approach with an instrument in the form of a questionnaire. The data from the research results were analyzed using the Partial Least Square analysis technique with the help of the SmartPLS 3.0 program. Based on the results of the analysis, several main findings were obtained: (1) Organizational transformation has a positive and significant effect on employee performance; (2) Leadership does not have a significant influence on employee performance; (3) Organizational transformation does not have a significant influence on organizational behavior; (4) Leadership has a positive and significant effect on organizational behavior; (5) Organizational transformation through organizational behavior does not have a significant influence on employee performance; (6) Leadership through organizational behavior does not have a significant influence on employee performance; (7) Organizational behavior does not have a significant influence on employee performance.